Moral Questions - Rhees, R. author. aut Link
XXXI, 261 p.
Keywords: Rush Rhees questions the viability of moral theories and the general claims they make in ethics. He shows how one can both be concerned with knowing what one ought to do while recognising that one's answer is a personal one. These insights, arrived at in a distinctive style, characteristic of Rhees, are then applied to issues of life and death, human sexuality and our relations to animals. To recognise why philosophy cannot answer such questions for us is an affirmation, not a denial, of their importance.